2014
DOI: 10.1007/s10509-014-1846-6
|View full text |Cite
|
Sign up to set email alerts
|

Effective dark energy models and dark energy models with bounce in frames of F(T) gravity

Abstract: Various cosmological models in frames of F (T ) gravity are considered. The general scheme of constructing effective dark energy models with various evolution is presented. It is showed that these models in principle are compatible with ΛCDM model. The dynamics of universe governed by F (T ) gravity can mimics ΛCDM evolution in past but declines from it in a future. We also construct some dark energy models with the "real" (non-effective) equation-of-state parameter w such that w ≤ −1. It is showed that in F (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…We take the interaction term Q to have the same form (37) as before. Solving the gravitational equation of motion (36) for dark matter, we find…”
Section: Little Ripmentioning
confidence: 99%
See 1 more Smart Citation
“…We take the interaction term Q to have the same form (37) as before. Solving the gravitational equation of motion (36) for dark matter, we find…”
Section: Little Ripmentioning
confidence: 99%
“…Recently the F (R) and F (T ) gravity models in the presence of a bounce cosmology were discussed in Refs. [35][36][37][38][39]. We will in the following study similar bounce cosmologies.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that, besides the model presented here, non-singular scenarios have been reported within models of f (R) theories of gravity in Palatini [171] and metric [172] formalisms, generalized teleparallel theories of gravity [173][174][175][176], bouncing in brane models [177][178][179][180][181] and modified Gauss-Bonnet gravity [182] (see also [183] for recent review). In [184], it is shown that a quantized neutral scalar field minimally coupled to classical gravitational field may avoid the singularity.…”
Section: Discussionmentioning
confidence: 74%
“…Recently the F (R) and F (T ) gravity models in the presence of bounce cosmology was discussed in Refs. [26,27]. We will in the following study similar bounce cosmologies.…”
Section: Introductionmentioning
confidence: 96%